2009
DOI: 10.2174/1874192400903010008
|View full text |Cite
|
Sign up to set email alerts
|

Early Results of Combined and Staged Coronary Bypass and Carotid Endarterectomy in Advanced Age Patients in Single Centre

Abstract: Aim:In present study, we aimed to compare the staged and combined surgery in patients with severe carotid stenosis and coronary atherosclerosis and detect the factors affecting mortality and morbidity.Material and method: Between 2004 and 2008, 120 patients with predominant ischemic heart disease were enrolled to study. Patients were divided into three groups on basis surgery procedure. Group 1 (n=40) includeed patients had coronary artery disease without carotid disease underwent coronary artery by-pass graft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
10
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 36 publications
2
10
0
Order By: Relevance
“…Other reports have found higher overall complications and higher hospital cost from staged as opposed to synchronous interventions [24], whereas some studies found no difference in length of stay or stroke rate between staged or synchronous procedures [12]. Our study is consistent with that by Ieym and colleagues [12] with an average length of stay of 7.5 days. We believe that staging CABG within 24 hours of CEA can minimize the risk of combined procedures by limiting prolonged anesthesia time and associated complications, as well as decreasing MI after CEA.…”
Section: Commentsupporting
confidence: 90%
See 4 more Smart Citations
“…Other reports have found higher overall complications and higher hospital cost from staged as opposed to synchronous interventions [24], whereas some studies found no difference in length of stay or stroke rate between staged or synchronous procedures [12]. Our study is consistent with that by Ieym and colleagues [12] with an average length of stay of 7.5 days. We believe that staging CABG within 24 hours of CEA can minimize the risk of combined procedures by limiting prolonged anesthesia time and associated complications, as well as decreasing MI after CEA.…”
Section: Commentsupporting
confidence: 90%
“…We believe that staging CABG within 24 hours of CEA can minimize the risk of combined procedures by limiting prolonged anesthesia time and associated complications, as well as decreasing MI after CEA. Cardiac events are the number one cause of death after CEA with 1.5% to 7.3% of patients having a perioperative MI [12,27]. In our study, 1 patient had an MI post-CEA prior to undergoing CABG.…”
Section: Commentmentioning
confidence: 56%
See 3 more Smart Citations